Miniature auto‐perfusion bioreactor system with spiral microfluidic cell retention device. Issue 5 (1st March 2021) - Yin, Lu; Au, Wen Y.; Yu, Chia C.; Kwon, Taehong; Lai, Zhangxing; Shang, Menglin; Warkiani, Majid E.; Rosche, Roger; Lim, Chwee T.; Han, Jongyoon
Abstract: Medium perfusion is critical in maintaining high cell concentration in cultures. The conventional membrane filtration method for medium exchange has been challenged by the fouling and clogging of the membrane filters in long‐term cultures. In this study, we present a miniature auto‐perfusion system that can be operated inside a common‐size laboratory incubator. The system is equipped with a spiral microfluidic chip for cell retention to replace conventional membrane filters, which fundamentally overcomes the clogging and fouling problem. We showed that the system supported continuous perfusion culture of Chinese hamster ovary (CHO) cells in suspension up to 14 days without cell retention chip replacement. Compared to daily manual medium change, 25% higher CHO cell concentration can be maintained at an average auto‐perfusion rate of 196 ml/day in spinner flask at 70 ml working volume (2.8 VVD). The auto‐perfusion system also resulted in better cell quality at high concentrations, in terms of higher viability, more uniform and regular morphology, and fewer aggregates. We also demonstrated the potential application of the system for culturing mesenchymal stem cells on microcarriers. This miniature auto‐perfusion system provides an excellent solution to maintain cell‐favorable conditions and high cell concentration in small‐scale cultures for research and clinical uses. Abstract : A miniature auto‐perfusion bioreactor system with a spiral microfluidic cell retention device was developed in this study. The clogging‐free cell retention technology, utilizing inertial microfluidics principles, was applicable to suspension cells and cell‐laden microcarriers. By continuous culture media perfusion, the system could maintain cell‐favourable conditions and high cell concentration in small‐scale long‐term cultures, which is suitable for research and clinical applications. α .